Neither angels nor heroes: nurse speeches during the COVID-19 pandemic from a Foucauldian perspective - Mariana Mendes; Juliana Silveira Bordignon; Robriane Prosdocimi Menegat; Dulcinéia Ghizoni Schneider; Mara Ambrosina de Oliveira Vargas; Evangelia Kotzias Atherino dos Santos; Priscila Rodrigues da Cunha (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to analyze the processes of meaning production, based on the speeches of nursing professionals, about how they feel about the titles of "angels and heroes" given by society during the pandemic of COVID-19. Methods: a qualitative, documentary research. Data was collected in October and November 2020 and analyzed from the perspective of the Discourse Analysis proposed by Michel Foucault. Results: they were organized into two thematic categories: "Angels and heroes? The (not) heroic reality of nursing during the pandemic" and "The search for recognition of the professional work of nursing: between what is said and what is not said". Final considerations: the nurses' speeches enunciate the search for decent conditions for the execution of care, fair wages, and recognition of the professional work by society.